Heart Failure With Type 2 Diabetes Mellitus: Association Between Antihyperglycemic Agents, Glycemic Control, and Ejection Fraction - Lin, Shu Ning; Phang, Kok Kit; Toh, Seng Hsiung; Chee, Kok Han; Zaman Huri, Hasniza (Frontiers in Endocrinology, 2020)
Background: Heart failure (HF) is associated with type 2 diabetes mellitus (T2DM). Antihyperglycemic drugs have interaction with heart failure among diabetic patients. To date, the data on real world use of diabetic medication in Malaysian heart failure patients with T2DM has not been elucidated. Objective: This study aims to identify the prescribing pattern of antihyperglycemic regimens in HF patients with T2DM, and to investigate the association between glycemic control and other factors such as demographic and clinical characteristics with left ventricular ejection fraction (LVEF) in these patients. Methods: This retrospective observational study involved patients diagnosed to have HF and T2DM who were seen in the outpatient clinic in a government tertiary hospital in Malaysia. Patients receiving at least one oral antidiabetic agent and/or insulin for at least 3 months prior were included. The differences and association between study outcomes were examined and analyzed using Pearson’s Chi-square test, One-Way ANOVA, Binary Logistic Regression and multiple Multinomial Logistic Regression models. Results: From July to December 2019, 194 patients were included in this study. The majority (52.1%) of the patients had HF with preserved ejection fraction (HFpEF), 20.6% had HF with mid-range EF (HFmrEF), and 27.3% had HF with reduced EF (HFrEF). Overall, metformin (59.8%) was the commonest antihyperglycemic agent prescribed, followed by insulins (54.0%), and sulphonylureas (44.9%). The most prescribed agents for HFpEF, HFmrEF, and HFrEF patients were metformin (65.3%), insulins (62.5%), and sulphonylureas (60.4%) respectively. The prescribing trend of sulphonylureas was found to be significantly associated with patients’ LVEF status (p=0.033). The odds for sulphonylurea prescription among the HFrEF patients were 2.42 times higher compared to the HFpEF patients (95% confidence interval [CI], 1.23-4.79). There was no association found between glycemic control with patients’ LVEF. Conclusion: Our findings reported metformin as the most commonly prescribed antihyperglycemic agent, sodium glucose linked transporter-2 (SGLT-2) inhibitor being under-prescribed, and detected poorly controlled diabetes in majority of patients with T2DM and HF. Understanding the prescribing pattern of antihyperglycemic agents supports the implementation of evidence-based treatment in HF patients with T2DM to improve patients’ outcomes.